RETRACTED: SUMBANGAN KOORDINASI MATA-KAKI, KELINCAHAN, KESEIMBANGAN DINAMIS DAN FLEKSIBILITAS TOGOK TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PERMAINAN SEPAKBOLA - Pratama, Andika Priya (Efektor, 2017)
RETRACTED Following a rigorous, carefully concerns and considered review of the article published in Journal Efektor to article entitled “SUMBANGAN KOORDINASI MATA-KAKI, KELINCAHAN, KESEIMBANGAN DINAMIS DAN FLEKSIBILITAS TOGOK TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PERMAINAN SEPAKBOLA” Vol 4, No 1, pp. 18-23, Mei 2017, DOI: https://doi.org/10.29407/e.v4i1.740. The document and its content has been removed from Journal Efektor, and reasonable effort should be made to remove all references to this article.